2022
DOI: 10.3389/fimmu.2022.1048505
|View full text |Cite
|
Sign up to set email alerts
|

The osteoblast secretome in Staphylococcus aureus osteomyelitis

Abstract: Osteomyelitis (OM) is an infectious disease of the bone predominantly caused by the opportunistic bacterium Staphylococcus aureus (S. aureus). Typically established upon hematogenous spread of the pathogen to the musculoskeletal system or contamination of the bone after fracture or surgery, osteomyelitis has a complex pathogenesis with a critical involvement of both osteal and immune components. Colonization of the bone by S. aureus is traditionally proposed to induce functional inhibition and/or apoptosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…This process involves RANKL, a molecule displayed on the membrane of osteoblasts that stimulates differentiation and resorptive activity of osteoclasts, leading to bone resorption. Previous studies on the interaction between bacteria and osteoblasts also found an increase in RANKL [ 36 , 54 , 55 ]. Culture supernatants from B. abortus -infected adipocytes induce RANKL expression in osteoblasts.…”
Section: Discussionmentioning
confidence: 78%
“…This process involves RANKL, a molecule displayed on the membrane of osteoblasts that stimulates differentiation and resorptive activity of osteoclasts, leading to bone resorption. Previous studies on the interaction between bacteria and osteoblasts also found an increase in RANKL [ 36 , 54 , 55 ]. Culture supernatants from B. abortus -infected adipocytes induce RANKL expression in osteoblasts.…”
Section: Discussionmentioning
confidence: 78%
“…Interestingly, an increase in mitochondrial fission in osteoblasts is also linked to an increase in the ratio of receptor activator of nuclear factor-kappaB ligand (RANKL) to osteoprotegerin (OPG) [ 54 ]. The RANKL/OPG ratio is a determinant of bone mass and skeletal integrity [ 55 ]. Thus, increased fission is connected to additional bone destruction, which furthermore suggests that the inhibition of fission might offer promising results in the treatment of osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…169 SCVs have also been detected in fibroblasts isolated from hip implant infections with prior treatment failures. 170 In response to S. aureus infections, osteoblasts produce host defense molecules including AMPs (LL-37 and β-defensins), upregulates TLR2 expression and a multitude of cytokines and chemokines important in immune recruitment (IL-6, IL-1β, TNF-α, CXCL10, CXCL9, CCL5) 162,171,172 (extensively reviewed in Granata et al 173 ).…”
Section: Nonimmune Cell Infection and Host-defensementioning
confidence: 99%
“…In response to S. aureus infections, osteoblasts produce host defense molecules including AMPs (LL‐37 and β‐defensins), upregulates TLR2 expression and a multitude of cytokines and chemokines important in immune recruitment (IL‐6, IL‐1β, TNF‐α, CXCL10, CXCL9, CCL5) 162,171,172 (extensively reviewed in Granata et al 173 ). Osteocytes also produce lipid mediators (prostaglandins) and cytokines (IL‐6) increase osteoblast antimicrobial efficiency 162 .…”
Section: Immune Repertoire Contributions During Infectionmentioning
confidence: 99%